Akuntabilitas dan Efektivitas Pengelolaan Dana Hibah Daerah (Studi Pada PMI Cabang Barru) - Zulfaidah; Rayhan Tri Arung (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
This study aims to analyze the accountability and effectiveness of regional grant fund management at the Indonesian Red Cross (PMI) Barru Branch. Accountability in grant fund management is crucial to ensure transparency, accountability, and legitimacy in the use of public funds. Furthermore, the effectiveness of grant fund use determines the extent to which a social organization's goals are achieved. This study used a qualitative approach using in-depth interviews and documentation. Informants included PMI Barru Branch administrators, local government officials, and beneficiaries. The results indicate that PMI Barru Branch has implemented accountability principles through financial reporting, internal audits, and information disclosure. However, several obstacles remain, including delays in fund disbursement, limited human resources in administrative management, and minimal public outreach. In terms of effectiveness, grant fund use is capable of supporting humanitarian activities, but program reach is not optimal. This study provides theoretical contributions to the study of nonprofit organization accountability and provides practical input for local governments and PMI in improving grant fund management mechanisms.